Sistem pengambilan keputusan untuk pemilihan lokasi usaha menggunakan metode electre berbasis website - Da Silva, Graciela; Lobo Soares, Jaime da Costa (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
Choosing a strategic business location is a key factor in building a successful enterprise, especially in Lautem Municipality, Timor-Leste. This area presents various opportunities for businesses such as grocery shops, small restaurants, repair workshops, and agricultural ventures. However, entrepreneurs often face challenges like poor road infrastructure, limited purchasing power, and inadequate transport access. This study developed a web-based Decision Support System (DSS) using the ELECTRE method to help business owners select the most suitable location. The system evaluates multiple location options based on important criteria such as population density, transportation access, and economic activity. By using this approach, entrepreneurs can reduce the risk of choosing an unprofitable location and improve their chances of success. The results show that implementing the ELECTRE method in a DSS is effective for identifying optimal business sites. These findings are expected to serve as a practical reference for entrepreneurs in Lospalos and nearby areas, while also supporting local economic development in the region.